Severe Groin Pain Following Transobturator Tape Procedure Necessitating Partial Removal of the Tape - Gökçe Anık İlhan; Orhan Ünal (Gynecology Obstetrics & Reproductive Medicine, 2015)
Groin pain after transobturator tape (TOT) procedure can occur; however, severe groin pain and difficulty in ambulating requring exploration of the obturator compartment and surgical excision of the tape is uncommon. We present a case with severe groin pain after uncomplicated TOT in which the patient could not stand the pain despite conservative treatment. Unlike most cases presented in the literature, the pain could only be releived by partial removal of the tape. Although TOT is an effective and safe procedure in the treatment of stress urinary incontinance, obturator nerve entrapment may rarely occur and mesh dissection and excision may be the only choice to releive the pain in these patients with untolerable severe symptoms.